2016
DOI: 10.2320/matertrans.l-m2016828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure Factors on Stress Corrosion Behavior of Mg<i>-x</i>Sn Alloys (<i>x</i> = 2, 5, 8 mass%)

Abstract: The effect of microstructure on the stress corrosion behavior of Mg-Sn alloys was investigated using a bent-beam method. The effects of an Mg 2 Sn phase and Sn in the matrix on stress corrosion were investigated. Mg 2 Sn phase mainly formed at the grain boundary. The volume fraction of the Mg 2 Sn phase increased with increasing Sn content, and the morphology of Mg 2 Sn changed from spherical to a semi-continuous network. The average volume fractions of Mg 2 Sn phase increased from 0.07 ± 0.02% to 5.06 ± 0.92%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Miller 32) reported that the alloys, AZ91, AM61, and AS41, interpreted to show a SCC threshold at 40-50% yield strength in distilled water. Thus, from previous studies and our previous work 15,23) , the applied stress was determined to 55 ± 5% yield strength and the elastic modulus of Mg-2Sn alloy was 45 GPa. Samples for the three-point bending tests were ground using silicon carbide abrasive papers to 4000 grit.…”
Section: Three-point Bending Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Miller 32) reported that the alloys, AZ91, AM61, and AS41, interpreted to show a SCC threshold at 40-50% yield strength in distilled water. Thus, from previous studies and our previous work 15,23) , the applied stress was determined to 55 ± 5% yield strength and the elastic modulus of Mg-2Sn alloy was 45 GPa. Samples for the three-point bending tests were ground using silicon carbide abrasive papers to 4000 grit.…”
Section: Three-point Bending Testmentioning
confidence: 99%
“…The Sn content in matrix also changed during ECAE process, which reduced about 15-25%. However, in our previous research 15) , we have studied the effect of matrix Sn content on stress corrosion test. We revealed that the effect of matrix Sn from 2 to 8% on SCC was slight and could be ignored.…”
Section: Microstructure Of Mg-2%sn Alloy After Ecae Processmentioning
confidence: 99%
See 1 more Smart Citation